Extracellular water to total body water ratio obtained by bioelectrical impedance analysis determines the dose intensity of lenvatinib for the treatment of patients with advanced hepatocellular carcinoma. Issue 6 (6th January 2021) - Yamaoka, Kenji; Kodama, Kenichiro; Hiramatsu, Akira; Ando, Yuwa; Kosaka, Yumi; Suehiro, Yosuke; Fujii, Yasutoshi; Uchikawa, Shinsuke; Morio, Kei; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; et al.
Abstract: Background and Aim: The aim of this study was to identify the factors that contribute to the maintenance of relative dose intensity (RDI) of lenvatinib in hepatocellular carcinoma (HCC) patients. Methods: Thirty‐two patients with advanced HCC treated with lenvatinib were enrolled. We evaluated the relationship between maintenance of RDI and various clinical data, parameters obtained by body composition measurements with bioelectrical impedance analysis (BIA) and grip strength at the start of lenvatinib treatment. Results: Multivariate analysis showed that only the extracellular water to total body water ratio (ECW/TBW) ≤ 0.400 at initiation of treatment was associated with RDI ≥ 50% (odds ratio, 6.94; 95% confidence interval [CI], 1.00–48.00; P =  0.049). When the RDI was compared between ECW/TBW ≤ 0.400 group and ECW/TBW > 0.400 group, the RDI was significantly higher in the ECW/TBW ≤ 0.400 group at each of 0–4W, 4–6W, and 6–8W points. The P value at each point was 0.003, 0.003, and 0.005, respectively. On the other hand, multivariate analysis showed that only the ECW/TBW ≤ 0.400 at initiation of treatment was associated with the extension of duration until reduction or withdrawal of lenvatinib (hazard ratio, 4.86; 95% CI, 1.52–15.50; P =  0.007). Conclusion: The extracellular water to total body water ratio, a parameter of body composition measurement by BIA, was significantly associated with the maintenance of RDI and the duration until reduction or withdrawal of lenvatinib in HCC patients. In addition to standard predictors such as Child–Pugh score and modified albumin‐bilirubin grade that have been used to date, ECW/TBW might be a new predictor of RDI in HCC patients treated with lenvatinib.